Novel microbiota Mesosutterella faecium sp. nov. has a protective effect against inflammatory bowel disease - Yu, Seung Yeob; Oh, Byeong Seob; Ryu, Seoung Woo; Bak, Jeong Eun; Heo, Eun Seo; Moon, Jeong Chan; Jeong, Jae-Ho; Lee, Ju Huck (Frontiers in Microbiology, 2024)
A novel Gram-negative, obligate anaerobe, non-motile, flagella-lacking, catalase-and oxidasenegative, coccobacilli-shaped bacterial strain designated AGMB02718 T was isolated from swine faeces. The 16S rRNA gene analysis indicated that strain AGMB02718 T belonged to the genus Mesosutterella with the highest similarity to M. multiformis 4NBBH2 T (= DSM 106860 T ) (sequence similarity of 96.2%), forming a distinct phylogenetic lineage. Its growth occurred at 25-45 ℃ (optimal 37 ℃) and in 0.5-1% NaCl (optimal 0.5%). Strain AGMB02718 T was asaccharolytic and contained menaquinone 6 (MK-6) and methylmenaquinone 6 (MMK-6) as the predominant respiratory quinones.The major cellular fatty acids in the isolate were C18:1 9c and C16:0. Based on the whole-genome sequencing analysis, strain AGMB02718 T had a 2,606,253 bp circular chromosome with a G+C content of 62.2%. The average nucleotide identity value between strain AGMB02718 T and M. multiformis 4NBBH2 T was 72.1%, while the digital DNA-DNA hybridization value was 20.9%. Interestingly, genome analysis suggested that strain AGMB02718 T possessed a low-toxicity lipopolysaccharide (LPS) because the genome of the isolate does not include lpxJ and lpxM genes for Kdo2-Lipid A (KLA) assembly, which confers high toxicity to LPS. Moreover, in vitro macrophage stimulation assay confirmed that AGMB02718 T produced LPS with low toxicity. Because the lowtoxicity LPS produced by the Sutterellaceae family is involved in regulating host immunity and lowtoxicity LPS-producing strains can help maintain host immune homeostasis, we evaluated the antiinflammatory activity of strain AGMB02718 T against inflammatory bowel disease (IBD). As a result, strain AGMB02718 T was able to prevent the inflammatory response in a dextran sulfate sodium (DSS)induced colitis model. Therefore, this strain represents a novel species of Mesosutterella that has a protective effect against DSS-induced colitis, and the proposed name is Mesosutterella faecium sp. nov.